2015
DOI: 10.1007/s40037-015-0198-4
|View full text |Cite
|
Sign up to set email alerts
|

Beyond work-hour restrictions: a qualitative study of residents’ subjective workload

Abstract: IntroductionFollowing the introduction of work-hour restrictions, residents’ workload has become an important theme in postgraduate training. The efficacy of restrictions on workload, however, remains controversial, as most research has only examined objective workload. The purpose of this study was to explore the less clearly understood component of subjective workload and, in particular, the factors that influenced residents’ subjective workload.MethodThis study was conducted in Japan at three community teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…[ 40 ] A qualitative study revealed that Japanese residents decreased their subjective workload when they felt that they could control their job and have a fulfilling personal life. [ 41 ] In addition, the Japan Society for Medical Education presented a draft version of the core competency of medical professionalism, which consisted of 7 subdomains, with “self-control and career development” included as one of the domains.…”
Section: Discussionmentioning
confidence: 99%
“…[ 40 ] A qualitative study revealed that Japanese residents decreased their subjective workload when they felt that they could control their job and have a fulfilling personal life. [ 41 ] In addition, the Japan Society for Medical Education presented a draft version of the core competency of medical professionalism, which consisted of 7 subdomains, with “self-control and career development” included as one of the domains.…”
Section: Discussionmentioning
confidence: 99%
“… 25 Our findings suggest that similar to patient safety, there are nuances to the theme of ‘resident well-being’ in the context of RDH, specific number of hours off between shifts and number of consecutive night floats. 26 …”
Section: Discussionmentioning
confidence: 99%
“…The limited Japanese research on mental health during residency also focuses on the influence of trainee psychological qualities (ability to cope with stress) and interpersonal relationships. 15,[38][39][40][41] The single Japanese study that trialed restriction of resident work hours identified no decrease in the prevalence of depression or burnout. 15 The other main distinguishing theme of Japanese residency was the breadth of clinical skills acquired, including facility with bedside procedures and radiology image interpretation.…”
Section: Themes and Acgme Core Requirementsmentioning
confidence: 99%